Irritant effect, prevention of blood feeding and toxicity of nets impregnated with different pyrethroids on An. stephensi - M.H. Hodjati,b, N. Mousavi & C.F. Curtis (Journal of Vector Borne Diseases, 2003)
A resistant strain of An. stephensi was confirmed to have high resistance to knock down and kill byfour different pyrethroids in bioassays in comparison with a susceptible strain. Permethrin, lambdacyhalothrinand deltamethrin were more irritant to the susceptible strain than the resistant asjudged by time for first take-off, but nets treated with alphacypermethrin appeared to be more irritantto the resistant An. stephensi than the susceptible. With all the pyrethroids tested, the resistantstrain spent a longer time in contact with a treated net, which was in contact with a human arm,than did the susceptible strain. With permethrin the resistant strain fed significantly more successfullythrough the treated netting than did the susceptible strain. With deltamethrin there was a nonsignificanttendency in the same direction in comparing the two strains. However, with alphacypermethrinthere was a non-significant tendency in the reverse direction. After 15 min in the cagewhich tested for the ability to feed through a pyrethroid treated net, observed mortality was higherwith the susceptible than the resistant strain. Thus there was no sign that the longer resting of theresistant strain on treated netting would compensate for the fact that a higher dose was needed tokill this strain. Such compensation has been suggested with West African An. gambiae where treatednets continue to work well against a highly resistant wild population. However, this does notseem to apply to our resistant An. stephensi.